Method for determining electroplasticization parameters and method for improving high-cycle fatigue performance of component

Through a combination of simulation and experiment, the optimal pulse current parameters are determined and the metal components after pre-deformation are subjected to electroplasticization, which solves the problem of insufficient high-period fatigue performance of metal components and achieves significant improvement of high-period fatigue performance without affecting service performance.

CN119558059AActive Publication Date: 2025-03-04HARBIN INST OF TECH
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411628694.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-11-14
Filing Date
2024-11-14
Publication Date
2025-03-04
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

In the prior art, metal components still have shortcomings in high-period fatigue properties, especially under alternating load conditions, the fatigue resistance of the components is difficult to meet safety and durability requirements.

Method used

Through a combination of simulation and experiment, the optimal pulse current parameters are determined, and these parameters are used to electroplasticize the pre-deformed metal components to improve high cycle fatigue performance. The specific steps include: pre-deformation treatment, establishing a crystal model, simulating electroplasticization treatment, screening pulse current parameters, conducting real tests and re-screening, and finally determining the optimal pulse current parameters.

Benefits of technology

Without affecting the service performance of the metal component under actual working conditions, the high-period fatigue performance of the metal component is significantly improved by eliminating microscopic stress concentration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119558059A_ABST
    Figure CN119558059A_ABST
Patent Text Reader

Abstract

The invention discloses a method for determining electroplastification parameters and a method for improving the high-cycle fatigue performance of a component, and belongs to the technical field of material processing. According to the scheme, the pre-deformation treatment is performed on the metal component sample to obtain the actually-measured grain structure and the actually-measured microstructure after the pre-deformation treatment, and the crystal model which is the same as the actually-measured grain structure and the actually-measured microstructure is established in a simulation mode; the method comprises the following steps: pre-deforming a metal component sample, simulating results obtained by performing electroplastification treatment on a crystal model by using multiple groups of pulse current parameters, screening out multiple groups of pulse current parameters meeting conditions in a simulation mode, and further performing real test on the pre-deformed metal component sample by using the screened-out multiple groups of pulse current parameters. And screening again in a test mode to obtain an optimal pulse current parameter. According to the scheme, the high-cycle fatigue performance of the metal component can be improved by eliminating microstress concentration under the condition that the service performance of the metal component under the actual working condition is not affected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material processing, and in particular to a method for determining electroplasticization parameters and a method for improving the high-cycle fatigue performance of a component. Background Art

[0002] With the rapid development of industries such as automobiles and aviation, many metal components are in working conditions of alternating loads. The fatigue resistance of metal components is crucial to the safety and durability of equipment such as automobiles and aircraft. The essential reason for fatigue failure is that defects such as dislocations and slip bands in metals cause high stress concentration under cyclic loads. High-cycle fatigue performance is particularly sensitive to microstructures. Dislocation entanglement areas are very likely to cause stress concentration during fatigue cycles, leading to the initiation of fatigue cracks here.

[0003] In the related art, a pre-deformation treatment method is used to improve the high cycle fatigue performance of metal components. However, there is still a problem that the high cycle fatigue performance of the components is insufficient. Summary of the invention

[0004] The present invention provides a method for determining electroplasticization parameters and a method for improving the high-cycle fatigue performance of components. The technical solution is as follows:

[0005] In one aspect, a method for determining electroplasticization parameters is provided, comprising:

[0006] Performing pre-deformation treatment on the metal component sample, and obtaining the measured grain structure and measured microstructure of the metal component sample after the pre-deformation treatment;

[0007] Based on the measured grain structure and microstructure, a crystal model identical to the measured grain structure and microstructure is established by molecular dynamics simulation method;

[0008] Using multiple groups of pulse current parameters to perform electroplasticization treatment on the crystal model, and screening out several groups of pulse current parameters that meet the conditions according to the electroplasticization treatment results;

[0009] The metal component samples after pre-deformation treatment were subjected to electroplasticization treatment using several groups of selected pulse current parameters, and the optimal pulse current parameters were selected again according to the electroplasticization treatment results.

[0010] In another aspect, a method for improving high cycle fatigue performance of a component is provided, comprising:

[0011] Based on the metal component to be processed, the combination of the pre-deformation treatment and the optimal pulse current parameters corresponding to the metal component to be processed is determined by using the above-mentioned method for determining the process parameters of the electroplasticization treatment;

[0012] Performing pre-deformation treatment on the metal component to be treated by using the treatment type and treatment degree of the pre-deformation treatment in the combination;

[0013] The optimal pulse current parameters in the combination are used to perform electroplasticization treatment on the metal component to be treated after pre-deformation treatment to obtain the treated metal component.

[0014] The technical solution provided by the present invention can at least bring the following beneficial effects

[0015] The metal component samples are pre-deformed to obtain the measured grain structure and measured microstructure after the pre-deformation treatment, and a crystal model identical to the measured grain structure and measured microstructure is established by simulation, and multiple groups of pulse current parameters are simulated to perform electroplasticization treatment on the crystal model, so as to screen out several groups of pulse current parameters that meet the conditions by simulation, and further use the screened groups of pulse current parameters to conduct real tests on the metal component samples after the pre-deformation treatment, and use the test method to screen again to obtain the optimal pulse current parameters. This scheme can select a combination of pre-deformation treatment and optimal pulse current parameters that improve the high-cycle fatigue resistance of the component by combining simulation and experiment, and then use this combination to perform electroplasticization treatment on the metal component, so as to improve the high-cycle fatigue performance of the metal component by eliminating microscopic stress concentration without affecting the service performance of the metal component under actual working conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0017] Figure 1 It is a flow chart of a method for determining process parameters of electroplasticization treatment provided by one embodiment of the present invention;

[0018] Figure 2 It is a flow chart of a method for improving high cycle fatigue performance of a component provided by one embodiment of the present invention. DETAILED DESCRIPTION

[0019] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0020] As mentioned above, the pre-deformation treatment method still has the problem of insufficient high-cycle fatigue performance of components.

[0021] Considering that the electron wind force generated by pulse current in metal components can promote dislocation movement, it can be used to regulate the internal microstructure of the component and change the mechanical properties of the material. However, for actual metal components, the mechanical properties of the material are closely related to the service performance of the component under actual working conditions. It is very difficult to improve its high-cycle fatigue performance without affecting the service performance of the component.

[0022] Based on this, the inventive concept of the present invention is to determine the optimal pulse current parameters through a combination of simulation and experiment, and to utilize the optimal pulse current parameters to perform electroplasticization on metal components, so as to improve the high-cycle fatigue performance of metal components by eliminating micro-stress concentration without affecting the service performance of metal components under actual working conditions.

[0023] The specific implementation of the above concept is described below.

[0024] Please refer to Figure 1 , an embodiment of the present invention provides a method for determining process parameters of electroplasticization treatment, the method comprising:

[0025] Step 100, performing a pre-deformation process on a metal component sample, and obtaining a measured grain structure and a measured microstructure of the metal component sample after the pre-deformation process;

[0026] Step 102, based on the measured grain structure and the measured microstructure, a crystal model identical to the measured grain structure and the measured microstructure is established by using a molecular dynamics simulation method;

[0027] Step 104, performing electroplasticization treatment on the crystal model using multiple sets of pulse current parameters, and selecting several sets of pulse current parameters that meet the conditions according to the electroplasticization treatment results;

[0028] Step 106 , using the selected groups of pulse current parameters to perform electroplasticization treatment on the metal component samples after the pre-deformation treatment, and selecting the optimal pulse current parameters again according to the electroplasticization treatment results.

[0029] In the embodiment of the present invention, a pre-deformation treatment is performed on a metal component sample to obtain the measured grain structure and measured microstructure after the pre-deformation treatment, a crystal model identical to the measured grain structure and measured microstructure is established by simulation, and multiple groups of pulse current parameters are simulated to perform electroplasticization treatment on the crystal model respectively, so as to screen out several groups of pulse current parameters that meet the conditions by simulation, and further use the screened several groups of pulse current parameters to conduct real tests on the metal component samples after the pre-deformation treatment, so as to screen again by test to obtain the optimal pulse current parameters. This scheme can select a combination of pre-deformation treatment and optimal pulse current parameters that improve the high-cycle fatigue resistance of components by combining simulation and test.

[0030] Described below Figure 1 How the various steps are performed.

[0031] First, with respect to step 100 , a pre-deformation treatment is performed on the metal component sample, and the measured grain structure and the measured microstructure of the metal component sample after the pre-deformation treatment are obtained.

[0032] In an embodiment of the present invention, if a metal component to be processed that needs to improve the high-cycle fatigue performance of the component has been determined, the metal component sample is the determined metal component to be processed; if a metal component to be processed that needs to improve the high-cycle fatigue performance of the component has not been determined, the metal component sample can be a component with any crystal structure and any metal material.

[0033] After obtaining the metal component sample, the high-cycle fatigue performance of the component can be initially improved by preliminarily using pre-deformation treatment.

[0034] In one embodiment of the present invention, the pre-deformation treatment includes one or more of shot peening, abrasive flow, deep rolling, laser shock peening and surface mechanical grinding; each treatment type includes at least one treatment degree. The pre-deformation treatment can cause uneven plastic deformation of the component and generate high-density dislocations inside the component.

[0035] The pre-deformation treatment in this step is a pre-deformation that determines the treatment type and treatment degree. Taking the treatment type as shot peening as an example, shot peening includes multiple treatment degrees, and each treatment degree has a corresponding degree of treatment parameters. For example, the pre-deformation treatment in this step is: shot peening, and the treatment degree is level one. It should be noted that when the treatment type includes multiple treatment degrees, the multiple treatment degrees can be set at intervals according to the upper and lower limit ranges of the treatment parameters.

[0036] In addition, the above-mentioned pre-deformation treatment can also be a combination of multiple treatment types, and each treatment type selects a corresponding treatment degree, thereby obtaining multiple combinations of pre-deformation treatments.

[0037] In an embodiment of the present invention, once the treatment type and degree of the pre-deformation treatment are determined, the subsequently determined optimal pulse current parameters form a combination with the pre-deformation treatment, which can be used to perform pre-deformation treatment and electroplasticization treatment on the same metal component as the metal component sample to improve the high-cycle fatigue performance of the component.

[0038] In order to obtain multiple combinations of pre-deformation treatments and optimal pulse parameters for improving the high-cycle fatigue performance of metal components that are the same as the metal component sample, in one embodiment of the present invention, the treatment type or degree of the pre-deformation treatment can be changed, and the method for determining the electroplasticization treatment process parameters can be repeatedly executed using the changed pre-deformation treatment to obtain the optimal pulse current parameters corresponding to the changed pre-deformation treatment.

[0039] In an embodiment of the present invention, the measured grain structure and measured microstructure of the metal component sample after pre-deformation treatment can be obtained in the following ways: the grain structure of the metal component sample after pre-deformation treatment is observed by scanning electron microscopy (SEM), electron backscatter diffraction (EBSD), etc., and the nanoscale microstructures such as dislocations and twins can be observed by transmission electron microscopy (TEM).

[0040] Then, for step 102 , based on the measured grain structure and the measured microstructure, a crystal model identical to the measured grain structure and the measured microstructure is established using a molecular dynamics simulation method.

[0041] In an embodiment of the present invention, in order to quickly obtain pulse current parameters suitable for metal component samples after pre-deformation treatment and reduce the cost of the entire process, a molecular dynamics simulation method can be used to establish a crystal model that is identical to the measured grain organization and measured microstructure, which is used to screen out the pulse current parameters through simulation means.

[0042] In one implementation, this step may specifically include the following steps 1020-1022:

[0043] Step 1020: using a molecular dynamics simulation method to establish a corresponding three-dimensional complete crystal for the metal component sample; the complete crystal is the actual crystal structure of the metal component sample, and the grain structure is the measured grain structure;

[0044] Step 1022: performing a pre-deformation process on the complete crystal to simulate the measured microstructure inside the complete crystal after the pre-deformation process, and obtaining a crystal model; wherein the pre-deformation process performed on the complete crystal is the same as the pre-deformation process performed on the metal component sample.

[0045] The molecular dynamics simulation software in the embodiment of the present invention may be Lammps, Materials studio, Ls1-MarDyn, IMD, CoMD, etc.

[0046] In order to ensure the accuracy of the simulation results and the subsequent selection of several pulse current parameters, the optimal pulse current parameters can be accurately obtained after the electroplasticization of the pre-deformed metal component samples during the test, and the simulation process is as close to reality as possible, that is, the pre-deformation treatment of the established complete crystal is the same as the pre-deformation treatment of the metal component samples, which is the same in terms of treatment type and degree. After the complete crystal is pre-deformed, the complete crystal is simulated to achieve the measured microstructure. At this time, the grain structure of the crystal model is the same as the measured grain structure, and the microstructure of the crystal model is the same as the measured microstructure.

[0047] Next, for step 104, the crystal model is subjected to electroplasticization treatment using multiple groups of pulse current parameters, and several groups of pulse current parameters that meet the conditions are screened out according to the electroplasticization treatment results.

[0048] In the embodiment of the present invention, it is necessary to first obtain multiple sets of pulse current parameters, wherein the pulse current parameters include: pulse period, pulse interval time, pulse current type, pulse waveform, current density amplitude and total pulse current processing time.

[0049] In the embodiment of the present invention, the ranges of the pulse current parameters are as follows:

[0050] The pulse period ranges from 0.01 to 10 ms;

[0051] The pulse interval time ranges from 0.005 to 10 ms;

[0052] The pulse current type is direct current or alternating current;

[0053] The pulse waveform is a square wave, a sine wave, a triangle wave, a sawtooth wave or a damped attenuation wave;

[0054] The current density amplitude ranges from 1 to 1000 A / mm 2 ;

[0055] The total pulse current treatment time is 1 to 10000 ms.

[0056] According to the range of the pulse current parameter, multiple groups of pulse current parameters can be obtained, and the parameter values ​​in each group of pulse current parameters are not completely the same.

[0057] After determining multiple groups of pulse current parameters, since the crystal model is obtained through molecular dynamics simulation software, each group of pulse current parameters can be used to perform electroplasticization treatment on the crystal model to simulate the electroplasticization treatment results.

[0058] Since the electron wind force generated by the pulse current in the metal component can promote the movement of dislocations and regulate the internal microstructure of the component to change the mechanical properties of the material, the electroplasticization treatment results are used to characterize the changes in the microstructure after the pulse current treatment.

[0059] In one embodiment of the present invention, when selecting several groups of pulse current parameters that meet the conditions according to the electroplasticization treatment results, it can specifically include: for multiple electroplasticization results corresponding to the multiple groups of pulse current parameters, determining whether the electroplasticization result is that the crystal only changes at the nanoscale but does not change at the microscale, and the amount of change in the microstructure meets the set conditions; if so, determining that the electroplasticization result meets the conditions, and selecting the pulse current parameters corresponding to the electroplasticization result.

[0060] If the crystal only changes at the nanoscale but not at the micrometer scale, it indicates that the grain structure does not change significantly.

[0061] The change of microstructure lies in the change of dislocation entanglement degree, dislocation density and the number of twins. If the dislocation entanglement degree decreases, the dislocation density decreases and the number of twins increases, it means that the microstructure is improved. Therefore, the setting condition can be a threshold value of the change amount of the corresponding microstructure parameter or the result of several maximum changes.

[0062] When the set condition corresponds to a threshold value of the change in microstructural parameters, for example, if the dislocation entanglement degree of the microstructure is reduced by at least A%, the dislocation density is reduced by at least B%, and the number of twins is increased by at least C% in the electroplasticization treatment result, it is determined that the change in the microstructure satisfies the set condition.

[0063] When the set condition is the result of several maximum changes, for example, several electroplasticization treatment results with the largest reduction in dislocation entanglement, the largest reduction in dislocation density, and the largest increase in the number of twins in the microstructure can be determined, and then several pulse current parameters can be determined. It should be noted that in this situation, if the maximum reduction in dislocation entanglement, the maximum reduction in dislocation density, and the largest increase in the number of twins in the same result cannot be achieved at the same time, a selection can be made according to a pre-set priority selection method to ensure that the selected electroplasticization treatment result has as large a reduction in dislocation entanglement, a larger reduction in dislocation density, and a larger increase in the number of twins as possible.

[0064] Finally, for step 106, the selected groups of pulse current parameters are used to perform electroplasticization treatment on the metal component samples after the pre-deformation treatment, and the optimal pulse current parameters are screened again according to the electroplasticization treatment results.

[0065] In one embodiment of the present invention, the electroplasticization treatment in this step may specifically include:

[0066] Step 1060: based on the number of the selected groups of pulse current parameters, obtaining the same number of pre-deformed metal component samples; wherein the same number of pre-deformed metal component samples are all the measured grain structures and the measured microstructures;

[0067] Step 1062: Corresponding a plurality of sets of pulse current parameters to the same number of pre-deformed metal component samples to form test pairs;

[0068] Step 1064: Using the pulse current parameters in the test pair to perform electroplasticization treatment on the metal component sample.

[0069] The actual electroplasticization treatment is carried out according to the selected pulse current parameters in an experimental manner. Therefore, after the metal component sample is subjected to an electroplasticization treatment, it cannot be restored to the next electroplasticization treatment. Therefore, it is necessary to obtain the metal component sample corresponding to each pulse current parameter. Try to ensure that the same number of metal component samples after pre-deformation treatment have the same measured grain structure and measured microstructure.

[0070] When using an experimental method to screen the optimal pulse current parameters, specifically, among the electroplasticization results corresponding to several test pairs, a target electroplasticization result can be determined in which the crystals only undergo changes on the nanoscale with the smallest change scale and the microstructure is improved the most, and the pulse current parameters corresponding to the target electroplasticization results are determined as the optimal pulse current parameters.

[0071] Similarly, the microstructure with the greatest improvement indicates the greatest reduction in dislocation entanglement, the greatest reduction in dislocation density, and the greatest increase in the number of twins. Moreover, in the same result, the three factors of the greatest reduction in dislocation entanglement, the greatest reduction in dislocation density, and the greatest increase in the number of twins cannot be achieved at the same time. They can be evaluated according to a pre-set comprehensive evaluation method to ensure that the comprehensive evaluation of the reduction in dislocation entanglement, the reduction in dislocation density, and the increase in the number of twins in the selected electroplasticization treatment result is the best.

[0072] The optimal pulse current parameters finally selected can keep the grain structure of the component unchanged while improving the microstructure, which can ensure that the mechanical properties (yield strength, tensile strength, elongation, etc.) of the component's own material do not change. Without affecting the service performance of the component under actual working conditions, the high-cycle fatigue performance of the component is improved by eliminating micro-stress concentration.

[0073] Please refer to Figure 2 The embodiment of the present invention also provides a method for improving the high cycle fatigue performance of a component, comprising:

[0074] Step 200: Based on the metal component to be processed, the combination of the pre-deformation treatment and the optimal pulse current parameters corresponding to the metal component to be processed is determined by using the method for determining the electroplasticization process parameters described in any of the above embodiments;

[0075] Step 202: performing pre-deformation treatment on the metal component to be treated by using the treatment type and treatment degree of the pre-deformation treatment in the combination;

[0076] Step 204: using the optimal pulse current parameters in the combination to perform electroplasticization treatment on the metal component to be treated after the pre-deformation treatment, to obtain a treated metal component.

[0077] The grain structure of metal components after electroplasticization treatment will not change significantly, but the microstructure can be effectively improved, thereby ensuring that the mechanical properties (yield strength, tensile strength, elongation, etc.) of the component's own material do not change. Without affecting the service performance of the component under actual working conditions, the high-cycle fatigue performance of the component is improved by eliminating micro-stress concentration.

[0078] Those skilled in the art can clearly understand that the present invention can be implemented by means of software plus a necessary general hardware platform. Based on such an understanding, the technical solution of the present invention can be essentially or partly embodied in the form of a software product that contributes to the prior art. The computer software product can be stored in a storage medium, such as ROM / RAM, a magnetic disk, an optical disk, etc., and includes several instructions for enabling a computer device (which can be a personal computer, a server, or a network device, etc.) to execute the methods described in various embodiments of the present invention or certain parts of the embodiments.

[0079] Finally, it should be noted that, in this article, relational terms such as first, second, third and fourth are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the statement "comprise a ..." do not exclude the presence of other identical elements in the process, method, article or device including the elements.

[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for determining process parameters of electroplasticization treatment, characterized in that: include: Performing pre-deformation treatment on the metal component sample, and obtaining the measured grain structure and measured microstructure of the metal component sample after the pre-deformation treatment; Based on the measured grain structure and microstructure, a crystal model identical to the measured grain structure and microstructure is established by molecular dynamics simulation method; Using multiple groups of pulse current parameters to perform electroplasticization treatment on the crystal model, and screening out several groups of pulse current parameters that meet the conditions according to the electroplasticization treatment results; The metal component samples after pre-deformation treatment were subjected to electroplasticization treatment using several groups of selected pulse current parameters, and the optimal pulse current parameters were selected again according to the electroplasticization treatment results.

2. The method according to claim 1, characterized in that The treatment types of the pre-deformation treatment include: one or more of shot peening, abrasive flow, deep rolling, laser shock peening and surface mechanical grinding; each treatment type includes at least one treatment degree.

3. The method according to claim 2, characterized in that Also includes: The treatment type or treatment degree of the pre-deformation treatment is changed, and the method for determining the process parameters of the electroplasticization treatment is repeatedly performed using the changed pre-deformation treatment to obtain the optimal pulse current parameters corresponding to the changed pre-deformation treatment.

4. The method according to claim 1, characterized in that: The method of establishing a crystal model identical to the measured grain structure and the measured microstructure by using a molecular dynamics simulation method based on the measured grain structure and the measured microstructure comprises: Using a molecular dynamics simulation method, a corresponding three-dimensional complete crystal is established for the metal component sample; the complete crystal is the actual crystal structure of the metal component sample, and the grain structure is the measured grain structure; The complete crystal is subjected to a pre-deformation treatment to simulate the measured microstructure inside the complete crystal after the pre-deformation treatment, thereby obtaining a crystal model; wherein the pre-deformation treatment performed on the complete crystal is the same as the pre-deformation treatment performed on the metal component sample.

5. The method according to claim 1, characterized in that The method of selecting a plurality of groups of pulse current parameters that meet the conditions according to the electroplasticization treatment results includes: For multiple electroplasticization results corresponding to multiple groups of pulse current parameters, determine whether the electroplasticization result is that the crystal only changes at the nanoscale but does not change at the microscale, and the change amount of the microstructure meets the set conditions. If so, it is determined that the electroplasticization result meets the conditions, and the pulse current parameters corresponding to the electroplasticization result are screened out.

6. The method according to claim 5, characterized in that The method of using the selected groups of pulse current parameters to perform electroplasticization treatment on the metal component samples after pre-deformation treatment includes: Based on the number of the selected groups of pulse current parameters, the same number of pre-deformed metal component samples are obtained; wherein the same number of pre-deformed metal component samples are all the measured grain structures and the measured microstructures; A test pair is formed by corresponding a plurality of groups of pulse current parameters to the same number of pre-deformed metal component samples; The pulse current parameters in the test are used to electroplasticize the metal component samples.

7. The method according to claim 6, characterized in that The method of selecting the optimal pulse current parameters again according to the electroplasticization treatment results includes: Determine the target electroplasticization result in which the crystal only undergoes nanoscale changes with the smallest change scale and the largest improvement in microstructure among the electroplasticization results corresponding to several test pairs, and determine the pulse current parameters corresponding to the target electroplasticization result as the optimal pulse current parameters.

8. The method according to any one of claims 1 to 7, characterized in that: The pulse current parameters include: pulse period, pulse interval time, pulse current type, pulse waveform, current density amplitude and total pulse current processing time.

9. The method according to claim 8, characterized in that The pulse period ranges from 0.01 to 10 ms; The pulse interval time ranges from 0.005 to 10 ms; The pulse current type is direct current or alternating current; The pulse waveform is a square wave, a sine wave, a triangle wave, a sawtooth wave or a damped attenuation wave; The current density amplitude ranges from 1 to 1000 A / mm 2 ; The total pulse current treatment time is 1 to 10000 ms.

10. A method for improving high cycle fatigue performance of a component, characterized in that: include: Based on the metal component to be processed, the combination of the pre-deformation treatment and the optimal pulse current parameters corresponding to the metal component to be processed is determined by using the method for determining the electroplasticization treatment process parameters described in any one of claims 1 to 9; Performing pre-deformation treatment on the metal component to be treated by using the treatment type and treatment degree of the pre-deformation treatment in the combination; The optimal pulse current parameters in the combination are used to perform electroplasticization treatment on the metal component to be treated after pre-deformation treatment to obtain the treated metal component.

Citation Information

Patent Citations

  • Method for preparing nanocrystalline / amorphous metal multi-layer film plastification through double-groove electrolysis

    CN106086963A

  • Low-cycle fatigue life prediction method considering microstructure influence

    CN111444602A

  • Method for reducing microstructure defects of cemented carbide based on pulse current

    CN111979505A

  • Metal additive manufacturing process system test design and structural data acquisition method

    CN112632724A

  • Fatigue crack initiation prediction method considering surface integrity

    CN114047210A